Comparison of Interleukin-13 and 15 Levels in Bacterial and Trichomonas Infection Isolated from Women of Childbearing and Menopausal Age - Sameen , Yousif Khidir; obaid, Hiro M.; Kader, Staar M. (South Eastern European Journal of Public Health, 2024)
Background: Trichomonas vaginalis is the causative agent of trichomoniasis, one of the most common sexually transmitted parasitic diseases worldwide. T. vaginalis primarily replicates in the epithelium during the initial infection of the genital mucosal surface. Innate immune cells and inflammatory reactions cause the release of anti-trophozoite cytokines. Trichomoniasis typically elicits aggressive local cellular immune responses with inflammation of the vaginal epithelium and exocervix in women and the urethra in men. T. vaginalis secretes a large number of cysteine proteinases (CPs) that break down various immunoglobulin types, enabling the parasite to evade the antibody response. Aim of the study: To assess the effect of trichomoniasis on some hematological markers, and serum IL-13 and IL-15 levels in women of childbearing age. Materials and Methods: This study was conducted in Kirkuk Governorate between November 10, 2023, and March 15, 2024. The total number of married, non-pregnant, and menopause women under study was 100, whose ages ranged from 18 to 59 years. A vaginal discharge specimen was collected from each participant to identify motile Trichomonas vaginalis through wet-mount microscopy. Blood samples were obtained for hematological assessment and immunological laboratory tests. Results: Of the 100 women in the study, 10 individuals (10%) had an infection with Trichomonas vaginalis. The study found significant differences in blood components between the T. vaginalis positive and negative groups, with the T. vaginalis positive group having higher average WBC levels, a lower lymphocyte count, and a higher eosinophil count. The study found no significant difference in IL-13 and IL-15 concentrations between the T. vaginalis positive and negative groups Conclusions: The T. vaginalis positive and negative groups did not significantly differ in their levels of IL-13 or IL-15, but they did differ in their immune cell counts. Specifically, the T. vaginalis positive group had a significant higher average level of white blood cells (WBC) and eosinophils but a lower mean lymphocyte count than the T. vaginalis negative group.